PENINGKATAN KESADARAN KEKAYAAN INTELEKTUAL KEPADA GRUP BAND TERHADAP HAK CIPTA DI WILAYAH DAERAH KHUSUS JAKARTA - Amelia, Sabina Putri; Abdullah, Nayla Putri; Yadila, Natasya; Reva Widiastiwi, Alisha; Camilla, Garneta Rizka; Jasmine, Nadya Fakhirah; Sabrina Putri, Raden Roro Iska; Rachman, Fahmi Aulia; Ramadhani, Isa Azizah; Mawaddah, Ananda Ratu; Ardian, Muhammad; Aryadana, Eka Putra; Ardian, Muhammad Fadhil (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2025)
Along with the rapid development of the music industry, bands in Jakarta often need help understanding the importance of copyright registration. This means that many of their works are not legally protected, so they risk being misused by other parties. Therefore, we, the community development team at the law faculty of the National Development University "Veteran" Jakarta, are trying to increase awareness regarding copyright for creators, especially in the music industry. In this way, we hope that as a community service team, creators can feel safe and that their work can be legally protected and provide sustainable economic benefits. The observation method is used when looking for target partners, which in this activity is the Manerole band group operating in the music industry. After observing, the next stage is socialization activities involving participants consisting of the general public and target partners. In this socialization, the basics of copyright law, copyright terms, exclusive rights obtained by creators, and a simulation of copyright registration, etc. were explained. The result of this activity was that the partner, namely the band Manerole, registered their creation entitled "Puppy Love".